The Impact of Using the Maternal Neonatal Emergency Application (SIGNAL) for Midwives - Sumarti Endah Purnamaningsih Maria Margaretha; Berlina Putrianti; Amri Wulandari; Dhiya Urrahman; Y Yohakim Marwanta (GLOBAL HEALTH SCIENCE GROUP, 2025)
Maternal mortality rate (MMR) and neonatal mortality rate (NMR) in Indonesia are still a challenge in health services. Technological innovations such as the SIGNAL application (Maternal Neonatal Emergency Information System) were developed to improve early detection of high risk in pregnant women and neonates. Objective to determine the impact of using the SIGNAL application for midwives in improving the speed and accuracy of maternal neonatal emergency services in Bantul Regency. Descriptive quantitative research with a cross-sectional approach was conducted on 50 midwives using SIGNAL at the Bantul Regency Health Center. The sampling technique used purposive sampling with a total of 50 respondents who actively used the SIGNAL application. Data were collected through questionnaires and analyzed descriptively. The results showed that 82% of midwives felt helped in early identification of high risk, 76% stated that referrals were faster, and 70% felt that the application increased confidence in making clinical decisions. The main obstacles were internet network and device limitations. The use of the SIGNAL application has a positive impact on improving the quality of maternal neonatal emergency services by midwives in Bantul Regency, although improvements in supporting infrastructure are still needed.